Sultan Agadez rebellion against French colonialism in the Ayar Desert 1916-1920 - betka, Ibrahim (The Algerian Historical Journal, 2026)
The rebellion of Sultan Agadez "Abd al-Rahim Tagama" against French colonialism in the period between 1916-1920, is one of the most important and largest rebellion that faced French colonialism in the desert of “Ayar” in the "Niger" territory, which almost ended its presence in the central desert of Africa, due to unification and alliance of all branches of the Tuareg tribes that participated this time, they were convinced and answered the call of Sultan Agadez who called for rebellion against the French. The use of modern weapons, in particular by the battalion of Tuareg officer "Kaossen", a senior guerrilla veteran of the “Senussi sufiorder” in the north, increased the complexity of the war for the French officers. Add to that, the extrem vastness of the Saharan “Ayar” region, especially since this revolution had coincided with the outbreak of the First World War, as France was engaged in protecting its vital area in Europe. and despite the failure of this revolution due of many circumstances, it remained a clear imprint and a bright page in the pages of the popular resistance of the Nigerian people, who continued to struggle even by political means after this rebellion, in order to gain independence.